An Analysis of Students’ Difficulties in Listening Comprehension at Senior High School - Windamayanti Windamayanti; Haryanto Atmowardoyo; Munir Munir (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2022)
The aim of this study is to find out the difficulties faced by students in listening. This research used a descriptive research method and was conducted at a senior high school in Polewali Mandar, West Sulawesi. Thirty-one students from the eleventh grade were selected as research subjects through a random sampling technique. The data was obtained from a questionnaire and an interview. The results obtained from the data analysis is the difficulties that students face when doing listening comprehension are; lack of vocabulary, students' interest in English, pronunciation, lack of concentration, accent, speaker talks too fast, topic changing, and they don't trust themselves.